Conceptual Art: between Idea and Technique (The International Journal for Scientific Research, 2026)
This research explores the creative interactions between idea and technique in conceptual art. It aims to define conceptual art as a movement, encompassing both idea and technique, and to reveal the forms of interaction between these two elements in conceptual artworks. The research also addresses artistic and technical issues that may contribute to understanding the relationship between ideas and techniques within the field of postmodern concepts. The author discloses how idea and technique harmonized in a sample of conceptual works, and points to the reasons that make these works open to both intellectual and technical interpretation. This research employs a descriptive-analytical approach followed by a comparative, interpretive, and conceptual methodology, considered the most suitable for a detailed analysis of the subject. It demonstrates various forms of interaction between idea and technique.The idea and technique may negate and simultaneously affirm each other, (as in the spiral water barrier). The idea may become the foundation of the technique (as in the work “One chair and three Chairs”). The idea may expand the scope of reality (as in “Hammering Man”), and both idea and technique may constitute a conceptual reality that does not yet exist (as in the work “Apotheosis of Homer”). The research concludes with several key points regarding the interaction between idea and technique. Most importantly, the diversity of techniques can contribute to giving a tangible character to the object depicted in the idea. The analyzed cases revealed that the idea becomes a prerequisite and a necessary condition for choosing the technique, controlling the presentation of the conceptual work, and understanding its meaning. Conceptual art formed through a hybrid technique that combines idea, form, and exhibition space. This hybridization is unlimited and unconditional, thus becoming the dominant principle of conceptual Art.
Keywords: Conceptual Art; Idea; Technique; Creative Interactions